21st century skills and their development : university teachers' perspective - Pàmies, Pilar Alonso (2019)
The discussion on the need for developing 21st century skills in higher education is a new phenomenon that demands research in the field. The aim of this study is to examine higher education teachers’ and managers’ as developers of 21st century skills. More specifically, the study focuses on the following two viewpoints. First, on the ways to support its development from the managers’ perspective. Second, the study aims to deepen understanding how their development contributes to university teachers’ identities and agency. This a qualitative study which utilised two models of semi-structured interviews in order to be able to answer the established research questions. The phenomenon was studied from the point of view of the selected managers (or HR figures) (n=2) and the university teachers (n=6) from two different university departments in Spain and in Finland. The data was examined through the thematic analysis. A total of four themes that contained the totality of the obtained data were identified. The main results point out how, overall, the selected departments are aware of the changes that the 21st century have set and therefore, work towards the development of them in order to improve their quality as providers of higher education. According to the findings regarding university teachers, some 21st century skills present a stronger need to develop, for instance, time management skills. Time management skills have also proven to be in relation-ship with other 21st century skills, such as creativity skills. Thus, the development of the first ones would potentially benefit the second ones. The main conclusion of this research focuses on creating cultures and environments in where individuals are continuously learning, which are aligned with promoting self-learning practices at the same time as setting a strong collaboration mindset.